2016
DOI: 10.5812/hepatmon.32215
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis A Virus and Hepatitis E Virus Seroprevalence Among Blood Donors in Tehran, Iran

Abstract: BackgroundHepatitis A virus (HAV) and Hepatitis E virus (HEV) are both transmitted by the fecal-oral route and are known as the leading causes of acute viral hepatitis in the world, especially in developing countries. There is a lack of updated data on HAV and HEV seroprevalence in Iran.ObjectivesThe aim of this study was to determine the seroprevalence of HAV and HEV among a group of blood donors in Tehran, Iran.Materials and MethodsA cross-sectional study was performed from July 2014 to December 2014, on a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 27 publications
2
13
2
Order By: Relevance
“…Similarly, Kaufmann et al had demonstrated a peak in seroprevalence of 5.3% in individuals aged 51 to 70 years old among blood donors in south west Switzerland. In Iranian blood donors' population, a similar increasing trend of HEV seropositivity was observed accounting for about 50% of HEV seropositive donors in the age group of >47 years …”
Section: Discussionsupporting
confidence: 62%
“…Similarly, Kaufmann et al had demonstrated a peak in seroprevalence of 5.3% in individuals aged 51 to 70 years old among blood donors in south west Switzerland. In Iranian blood donors' population, a similar increasing trend of HEV seropositivity was observed accounting for about 50% of HEV seropositive donors in the age group of >47 years …”
Section: Discussionsupporting
confidence: 62%
“…It seems that some countries like Iran are passing from intermediate-to lowendemicity area for HAV infection. Therefore, the role of vaccination should be highlighted in these countries (23).…”
Section: Discussionmentioning
confidence: 99%
“…Anti-HEV IgG antibodies increase to their peak level by the end of the fourth week and can continue for years (El-Tras et al 2013). HEV is generally transmitted by the fecaloral route, following transfusion with infected blood products, through vertical transmission and also through contact with infected animals (Hesamizadeh et al 2016). Individuals considered to be at high risk of contracting the virus include employees of slaughterhouses, people working on pig farms and veterinarians (Holt et al 2016).…”
Section: Introductionmentioning
confidence: 99%